Fungal Laccases: Production, Function, and Applications in Food Processing - Brijwani, Khushal (SAGE-Hindawi Access to Research, 2010)
Laccases are increasingly being used in food industry for production of cost-effective and healthy foods. To sustain this trend widespread availability of laccase and efficient production systems have to be developed. The present paper delineate the recent developments that have taken place in understanding the role of laccase action, efforts in overexpression of laccase in heterologous systems, and various cultivation techniques that have been developed to efficiently produce laccase at the industrial scale. The role of laccase in different food industries, particularly the recent developments in laccase application for food processing, is discussed.